„Good Internships” – support for gaining professional competences by the students of pedagogy at the University of Wrocław - Ewa Musiał (Konteksty Pedagogiczne, 2018)
Achieving high standards in the field of professional preparation of students-future teachers of a younger child is possible only thanks to the synergy of theory and practice. Participation in internship programs creates, alongside pedagogical on-the-job training, perfect conditions for acquiring and developing professional competences of future teachers through personal experience. Dur-ing the internship, the student may undertake a number of initiatives requiring knowledge – action and reflection. In this way, academic theory and practice integrate and accentuate, filling the space of professional competences, in which the inquisitiveness, creativity and openness of the student, its active and sys-tematic search for knowledge, criticism of research, reflexivity and analytical ap-proach to educational problems are of great importance. Scientific confrontation and practical viewing of reality, a fusion of scientific thinking with action in solving real problems also favors the construction of own educational theories. In addition, it combines two learning strategies: before and during the action, constituting a kind of bridge between academic knowledge and educational real-ity. It is a circumstance for the emergence of the category of “becoming a teacher” through getting to know oneself, one’s possibilities and limitations, as well as a conscious development of a working technique.